A few reflections on the current state of play for not-for-profit taxation arrangements - Pinto, Dale; Gilchrist, David; Morgan, Annette (Taxation Institute of Australia, 2013)
In its Budget handed down in May 2011, the federal government announced proposed new taxation arrangements covering the not-for-profit sector in Australia. The government explained that these arrangements were largely made in response to recent court cases pertaining to the taxation status of not-for-profit organisations (NFPs), with regard to trading income in particular. Currently, NFPs enjoy a range of tax concessions at the federal and state/territory level based on a relatively complex set of legislated and regulated arrangements. In utilising these concessions, NFPs can obtain a range of benefits for themselves and their employees. However, with the proposed new tax arrangements, these concessions can be at risk if NFPs do not understand the key changes and what they mean. In this article, the authors reflect on the current state of play in relation to not-for-profit tax arrangements and recent announcements by the government in relation to these concessions. In examining the government announcements, the article seeks to look to the future and take a preliminary view of the likely outcomes for NFPs.